Diagnosis of Food Insecurity and Nutritional Statusof users of the popular restaurants in the Northeast and South of Brazil. - Suwellen de Resende MORAES; Kátia GODOY; Karin Savio de OLIVEIRA (Universidade de Brasília, 2015)
Food insecurity occurs when the unmet nutritional needs cause psychological and physiological problems. Thinking about this panorama, this cross-sectional study aimed to evaluate the relationship between food insecurity and overweight in the Northeast and South. We used a form to identify the socioeconomic and demographic variables, was also made the calculation of BMI, and applied the Brazilian Scale of Food and Nutritional Insecurity in two regions of Brazil where 807 people were interviewed and 503 in the Northeast region and 304 in the South region. The most prevalent share of family income in both regions was that between ½ to 1 minimum wage. The Northeast region had a higher prevalence of users in food insecurity over the southern region, also presented more socioeconomic differences as lower education and income per capita, a higher proportion of unemployed and users in Food Insecurity in relation to the South. This fact is explained by population have a higher proportion of unemployed and a lower per capita income, leading to reduced power of access to food. Regarding nutritional status, in both regions there was overweight. This data may be indicative of the accelerated process of nutritional transition that lives the Brazilian population.